2020
DOI: 10.1155/2020/2571534
|View full text |Cite
|
Sign up to set email alerts
|

Dimension and Location of the Mandibular Lingula: Comparisons of Gender and Skeletal Patterns Using Cone-Beam Computed Tomography

Abstract: Objective. The study aimed to investigate and measure the anatomical relationship between the mandibular lingula (Li) and skeletal patterns using cone-beam computed tomography (CBCT). Materials and Methods. In total, 72 participants (23 men and 49 women) were categorized into three groups according to their skeletal patterns (specifically, the A point–nasion–B point (ANB]) angle) as follows: Class I (0° < ANB < 4°), Class II (ANB ≥ 4°), and Class III (ANB ≤ 0°). The CBCT images of 144 rami were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 13 publications
4
37
0
Order By: Relevance
“…The vertical distance between the lower mandibular margin and Spix’s spine (VDLiMB) was measured on the frontal plane passing through the apex of Spix’s spine as the distance from the apex of the Li to the lowest point of the mandible [ 3 , 6 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vertical distance between the lower mandibular margin and Spix’s spine (VDLiMB) was measured on the frontal plane passing through the apex of Spix’s spine as the distance from the apex of the Li to the lowest point of the mandible [ 3 , 6 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The strengths of correlations were described for the absolute values of the ratios of the compared variables as follows: very weak (0–0.19), weak (0.20–0.39), moderate (0.40–0. 59), strong (0.60–0.79), and very strong (0.80–1.0) [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [11][12][13] have demonstrated the relationship between the position of the antilingula and that of the lingula and mandibular foramen. Scholars [13][14][15] have suggested that the position of the antilingula-which can be seen during operation-exhibited a stable relationship with the position of the mandibular foramen.…”
Section: Discussionmentioning
confidence: 99%
“…As well as the mental foramen, other studies have evaluated different structures by using CBCT for predicting sex. Position of the mandibular lingual [16], volume of the mandibular condyle [17] and angulations of the mandibular fossa and articular tubercle [18] are structures which were shown to be useful to estimate the sex of individuals. However, it is known that bone structures of the temporomandibular joints (TMJ) are often subject to being affected by degenerative processes (e.g.…”
Section: Discussionmentioning
confidence: 99%